Determinación de la dosis terapetica de la infusion del Paico (Chenopodium ambrosioides) para el control de Ancylostoma spp. en caninos de la Fundacion Caridad Animal (2013)
This resecar was carried out in the municipality Piedecuesta (Santander) in canine of the fundation Animal Charity, looking for economic alternatives which do not affect the environment and contribute to diminish all the secondary effects of the antiparasites for a long time in animals. The objective was to look for a therapeutic dose of the infusión of the dry leaves of Paico (Chenopodium ambrosioides), which could be used as a natural antiparasite in canine with parasitosis by nematodos of the gender Ancylostoma. With this objective, 45 male and female ovariohisterectomized canine were chosen, between one and six years aged which were positive in the coprologycal test and which had charges of 1000 and up eggs by gran of feces (hpg), which were divided at random in three homogeneous groups of 15 animals each one. These were identified with yellow(A), blue(B) and red(C) collars. It was supplied the infusión of grounded dry leaves and dissolvent (15 gr/L) to each group oral way in different dose for 2 days and the third day lactulosa was supplied as a laxative to facilitate the expulsión of the parasites of the intestine. A following of the parasite charges was done by means of coproparasitologyc diagnosis in the 7th, 14th and 21st post-aplication. The treatments were managed: the group A drank the lowest dose (0.05 ml/kg), the group B the following dose (0.1 ml/kg) and the group C a dose of 0.15 ml/kg of living weight. The results obtained show that the desparasite with the infusión of Paico, presented a percentaje of reduction in the number of eggs in feces in all the studied groups, comparing the averages from the day 0 to the 21st, being very similar in the group B (99.01%) and the group C (98.76%). The group A with the lowest dose, shows a decrease of 87.13%. Taking in to account these percentajes, we can deduce that the usage of Paico as a natural antiparasite, represents a real posibility to replace the usage of pharmac and diminish in this species, adverse effects and maintenance costs.